2023
DOI: 10.1101/2023.05.17.541145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single nuclei transcriptomics in human and non-human primate striatum implicates neuronal DNA damage and proinflammatory signaling in opioid use disorder

Abstract: The striatum in the brain is involved in various behavioral functions, including reward, and disease processes, such as opioid use disorder (OUD). Further understanding of the role of striatal subregions in reward behaviors and their potential associations with OUD requires molecular identification of specific striatal cell types in human brain. The human striatum contains subregions based on different anatomical, functional, and physiological properties, with the dorsal striatum further divided into caudate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 151 publications
(247 reference statements)
0
2
0
Order By: Relevance
“…To harmonize annotations of striatal projection neuron subtypes across species and datasets, we analyzed eight published, annotated datasets in an unbiased manner, representing the broadest overview of single-nuclei RNA-seq and ATAC-seq data sampled from each species: mouse 4547,53 , rat 51 , rhesus macaque 48 , and human 49,50,54 . The inclusion criteria for these comparative analyses are: 1) publicly availability of the data, 2) the data are annotated, 3) inclusion of single-cell or nuclei RNA-seq or ATAC-seq approaches, 4) from any striatal subregion, and 5) from a mammal.…”
Section: Methodsmentioning
confidence: 99%
“…To harmonize annotations of striatal projection neuron subtypes across species and datasets, we analyzed eight published, annotated datasets in an unbiased manner, representing the broadest overview of single-nuclei RNA-seq and ATAC-seq data sampled from each species: mouse 4547,53 , rat 51 , rhesus macaque 48 , and human 49,50,54 . The inclusion criteria for these comparative analyses are: 1) publicly availability of the data, 2) the data are annotated, 3) inclusion of single-cell or nuclei RNA-seq or ATAC-seq approaches, 4) from any striatal subregion, and 5) from a mammal.…”
Section: Methodsmentioning
confidence: 99%
“…While this division is critical for understanding striatal physiology 25 , circuitry 26 , and molecular responses to drugs of abuse [27][28][29] , both cell populations express Oprm1 30 and contribute to opioidinduced behaviors 31 . Further, recent single nucleus RNA sequencing (snRNA-seq) studies have revealed unexpected heterogeneity in MSNs within the NAc and broader striatum, with multiple subtypes of Drd1 and Drd2 expressing MSNs present in the mouse 32 , rat [33][34][35] , monkey 36,37 , and human NAc 37,38 . Strikingly, NAc MSN subtypes exhibit highly variable expression of Oprm1 34 , highlighting the need for further investigation into the roles of distinct MSN subclasses in opioid action.…”
Section: Introductionmentioning
confidence: 99%
“…While this division is critical for understanding striatal physiology [ 25 ], circuitry [ 26 ], and molecular responses to drugs of abuse [ 27 29 ], both cell populations express Oprm1 [ 30 ] and contribute to opioid-induced behaviors [ 31 ]. Further, recent single nucleus RNA sequencing (snRNA-seq) studies have revealed unexpected heterogeneity in MSNs within the NAc and broader striatum, with multiple subtypes of Drd1 and Drd2 expressing MSNs present in the mouse [ 32 ], rat [ 33 35 ], monkey [ 36 , 37 ], and human NAc [ 37 , 38 ]. Strikingly, NAc MSN subtypes exhibit highly variable expression of Oprm1 [ 34 ], highlighting the need for further investigation into the roles of distinct MSN subclasses in opioid action.…”
Section: Introductionmentioning
confidence: 99%